Logistik Regression Analysis of Factor Influencing Drung Abuse Cases for Inmates in Class IIA Parepare Prison - Ale Miftahulhaer, Ale Miftahulhaer; Wahidah Alwi; Adnan Sauddin; Khalilah Nurfadilah (Jurusan Matematika FMIPA UNM, 2025)
Drugs are addictive substances that can have a negative impact on the body, especially on the central nervous system. Drug abuse can be caused by various factors including parental influence, knowledge, attitudes, family structure, peer pressure, and community environment. The purpose of this study was to identify the factors asociated with drug abuse cases in Class IIA Parepare Prison. The sample consisted of 85 respondebts from cases related to drug abuse in the prison. Logistic regression analysis was ued, with drug abuse status (using drugs/not using drugs) as the dependent variable and gender, age, knowledge, family, peers, and community environment as independent variables. The results of this study indicate that a high level of knowledge has a regression odds ratio of 13.6489. This indicate that inmates with higher knowledge about drugs had a significantly greater likelihood of avoiding drug abuse compared to those with lower knowledge.